2008
DOI: 10.1097/dad.0b013e3181834acd
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Ganglioneuroma Associated With Overlying Hyperkeratotic Epidermal Changes: A Report of 2 Cases

Abstract: The occurrence of primary cutaneous ganglioneuroma is rare. We report 2 separate cases of primary cutaneous ganglioneuroma, both of which are associated with prominent overlying hyperkeratosis. The first case was in a 38-year-old woman with overlying verrucous keratosis. The second case was in a 93-year-old man with epidermal changes reminiscent of a seborrheic keratosis. Histologically, both lesions were composed of a proliferation of hyperplastic nerve fibers with spindled Schwann cells and axons with interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Although ganglioneuroma is mostly a well-circumscribed mass, our case was not a circumscribed mass. Some ganglioneuroma in skin and colon were not a circumscribed mass [4,9]. It is possible that ganglioneuroma, especially in the choristomatous lesion, cannot form a circumscribed mass.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although ganglioneuroma is mostly a well-circumscribed mass, our case was not a circumscribed mass. Some ganglioneuroma in skin and colon were not a circumscribed mass [4,9]. It is possible that ganglioneuroma, especially in the choristomatous lesion, cannot form a circumscribed mass.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, ganglion cells are not normal components of the skin, but cutaneous ganglioneuroma may arise from immature precursors derived from neural crest, or they may be choristomas [9]. Glial polyps of the cervix or glial tissues in the cervix can exist [10,11] as a polypoid lesion composed of finely eosinophilic tissue with fully differentiated astrocytic glial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal GN have also been reported in the context of MEN 2A and MEN 2B, in addition to rare reports of MEN 2 in association with composite pheochromocytoma/GN . Primary cutaneous GN are extremely rare, as only 18 cases have been reported in the English literature to date, 16 of which are clear‐cut GN (Table ) …”
Section: Discussionmentioning
confidence: 99%
“…Primary GN is exceptional. Since the first observation in 1972 by Collins et al, only 16 cases have been reported in the English literature to date . Most of these cases show epidermal changes above the lesion.…”
Section: Introductionmentioning
confidence: 99%
“…En ocasiones pueden secretar polipéptidos intestinalmente vasoactivos, induciendo entonces un síndrome caracterizado por diarrea, hipopotasemia y aclorhidria 28 , o testosterona, lo que conlleva virilizaciones 7 . Se han descrito ubicaciones en cualquier zona del organismo: supratentoriales 3 , cerebelosas 15 , raquídeas 4,8,10,12,13,24 , mediastínicas 27 , retroperitoneales 22 , intestinales 11 o cutáneas 6 . Cuando su localización es cercana a la medula espinal es frecuente la compresión de la misma o la tracción radicular, pudiendo causar dolor, pér-dida de fuerza o trastornos sensoriales en dependencia del nivel mielo-radicular afecto.…”
Section: Discussionunclassified